Economic and environmental competitiveness of high temperature electrolysis for hydrogen production. (15th June 2021) - Motazedi, Kavan; Salkuyeh, Yaser Khojasteh; Laurenzi, Ian J.; MacLean, Heather L.; Bergerson, Joule A.
Abstract: Alternative hydrogen production technologies are sought in part to reduce the greenhouse gas (GHG) emissions intensity compared with Steam Methane Reforming (SMR), currently the most commonly employed hydrogen production technology globally. This study investigates hydrogen production via High Temperature Steam Electrolysis (HTSE) in terms of GHG emissions and cost of hydrogen production using a combination of Aspen HYSYS® modelling and life cycle assessment. Results show that HTSE yields life cycle GHG emissions from 3 to 20 kg CO2e /kg H2 and costs from $2.5 to 5/kg H2, depending on the system parameters (e.g., energy source). A carbon price of $360/tonne CO2e is estimated to be required to make HTSE economically competitive with SMR. This is estimated to potentially decrease to $50/tonne CO2e with future technology advancements (e.g., fuel cell lifetime). The study offers insights for technology developers seeking to improve HTSE, and policy makers for decisions such as considering support for development of hydrogen production technologies. Highlights: Highlighting economic and environmental trade-offs of high temperature electrolysis. Aspen HYSYS® modelling and life cycle assessment of high temperature electrolysis. Emissions of 3–20 kgCO2 e/kgH2 and cost of $2.5–5/kgH2 are possible. Carbon price of $50-$360 might been needed to make the process competitive with SMR.